Supported TiO2 in Ceramic Materials for the Photocatalytic Degradation of Contaminants of Emerging Concern in Liquid Effluents: A Review - Danfá, Sadjo (2021)
The application of TiO2 as a slurry catalyst for the degradation of contaminants of emerging concern (CEC) in liquid effluents has some drawbacks due to the difficulties in the catalyst reutilization. Thus, sophisticated and expensive separation methods are required after the reaction step. Alternatively, several types of materials have been used to support powder catalysts, so that fixed or fluidized bed reactors may be used. In this context, the objective of this work is to systematize and analyze the results of research inherent to the application of ceramic materials as support of TiO2 in the photocatalytic CEC removal from liquid effluents. Firstly, an overview is given about the treatment processes able to degrade CEC. In particular, the photocatalysts supported in ceramic materials are analyzed, namely the immobilization techniques applied to support TiO2 in these materials. Finally, a critical review of the literature dedicated to photocatalysis with supported TiO2 is presented, where the performance of the catalyst is considered as well as the main drivers and barriers for implementing this process. A focal point in the future is to investigate the possibility of depurating effluents and promote water reuse in safe conditions, and the supported TiO2 in ceramic materials may play a role in this scope.